2020
DOI: 10.1042/bsr20192620
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of protease-activated receptor 2 ameliorated osteoarthritis in rats through regulation of MAPK/NF-κB signaling pathwayin vivoandin vitro

Abstract: Recently, protease-activated receptor 2 (PAR2) has been proved to be involved in the inflammatory response including osteoarthritis (OA). In the present study, we found that PAR2 antagonist could remarkably improve the pathological condition of OA rats in vivo. In addition, we also found that PAR2 antagonist could suppress the production of inflammatory factors (TNF-α and Cox-2), decrease the levels of MMP-1 and MMP-13, and restrain the levels of P62 proteins and aggravate the expression of LC3-II both in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Measured levels of PAR-2 correlated with the severity of the synovitis, suggesting that PAR-2 is relevant in joint disease where there is ongoing inflammation. In other experiments, blocking PAR-2 reduced pannus invasion and proliferation, decreased the release of IL-17, IL-1β, and TNF-α, and ameliorated signs of OA via regulation of the MAPK/NF-kB pathway [50,98,99].…”
Section: Par-2 and Jointsmentioning
confidence: 86%
“…Measured levels of PAR-2 correlated with the severity of the synovitis, suggesting that PAR-2 is relevant in joint disease where there is ongoing inflammation. In other experiments, blocking PAR-2 reduced pannus invasion and proliferation, decreased the release of IL-17, IL-1β, and TNF-α, and ameliorated signs of OA via regulation of the MAPK/NF-kB pathway [50,98,99].…”
Section: Par-2 and Jointsmentioning
confidence: 86%
“…The results above suggest that PAR-2 plays a vital role in the occurrence and progression of OA. Therefore, the PAR-2 antagonist AZ3451 inhibits chondrocyte apoptosis to improve OA by activating chondrocyte autophagy by regulating the P38/MAPK, NF-κB, and PI3K/AKT/mTOR signaling pathways ( Huang et al, 2019 ; Yan et al, 2020 ).…”
Section: Protease-activated Receptorsmentioning
confidence: 99%
“…Destruction or mutation of GPCRs can lead to bone and joint dysfunction or diseases in humans, and most of these phenotypes have been validated in mouse models ( Luo et al, 2019 ). Furthermore, emerging evidence has shown that GPCRs regulate the progression of OA by modulating cartilage matrix degradation, synovial inflammation, subchondral bone remodeling, osteophyte formation, chondrocyte hypertrophy, cartilage angiogenesis, and chondrocyte apoptosis ( Jones et al, 2006 ; Yan et al, 2020 ; Mlost et al, 2021 ; Wang et al, 2021 ). However, the detailed mechanisms underlying the regulatory responses remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the effect of PAR2 antagonists in a pre-clinical aspect and showed that PAR2 blockage reduced disease progression and improved synovitis in adjuvant-induced monoarthritic mice models 21 . In addition to that, Yan et al found that down-regulation of PAR2 could ameliorate OA through suppressing the release of in ammatory factors and proteases and promoting chondrocytes proliferation via regulation of MAPK/NF-κB signaling 22 . Furthermore, apart from PAR2 contribution to synovitis and cartilage destruction, a mice study from 2015 has been clearly shown that PAR2 contributes to osteophyte formation via its presence in proliferative and hypertrophic chondrocytes 23 .…”
Section: Introductionmentioning
confidence: 99%